Refinements of Various Types of Fractional Inequalities via Generalized Convexity - Yong Tang; Ghulam Farid; M. Y. Youssif; Zakieldeen Aboabuda; Amna E. Elhag; Kahkashan Mahreen (Journal of Mathematics)
This paper aims to find generalizations of inequalities that hold for unified integral operators by applying strongly exponentially α,ℏ−m−p-convex functions. These inequalities generate results for several fractional integral operators and simultaneously hold for convex, strongly convex, and exponentially convex functions. The particular cases of presented inequalities are directly connected with many recently published results.